Löydöt arvopuntarissa. Arkeologisten esinelöytöjen valikoitumisesta museon kokoelmiin. - Seppänen Liisa; Helamaa Maija; Takala Hannu (Suomen Museo – Finskt Museum, 2022)
Weighing the value. Experiences and thoughts on the evaluation and preservation of archaeological finds.
Excavations of historical times often reveal an abundance of finds that cannot be saved in its entirety neither for practical reasons, nor even on research grounds. The classification of the finds that are either saved or discarded takes place mainly in the post-excavation phase and is based on an evaluation of the finds and an assessment of their significance for the research. Although decisions to preserve or discard the finds are based on the decision-makers ́ subjective views, they are also limited by the organizations’ collection policies and guidelines as well as practical realities such as availability of resources and challenges related to the preservation and maintenance of the material.
In this article, the authors explore how archaeological finds are valued in Finland and on what grounds they are selected for museum collections. As a case study, the article presents the criteria and perspectives that were applied when making decisions on the preservation of finds from excavations in Lahti in 2013. After the evaluation, majority of the finds was discarded and only about 30 percent of finds (according to find numbers) was selected for museum ́s collections. Based on the find number, only about 30 per cent of the finds ended up in the museum’s collections. Evaluation of the finds was primarily based on the archaeological and scientific value of the artefacts and the context of the finds.
However, studies of textiles classified as discarded have demonstrated that waste even from secondary contexts also contains significant research potential. This significance is difficult to assess without a closer examination and a special expertise in the material. In this article, we want to raise discussion on the evalua-tion and preservation of archaeological finds and research on this topic.